Evaluasi Permasalahan Layanan pada Sistem Reservasi Ruang Kelas Universitas XYZ Menggunakan COBIT 5 DSS02 - Diesti Hidayani; Fachruddin Edi Nugroho Saputro (Universitas Muhammadiyah Klaten, 2025)
The classroom reservation system is an information technology service that plays a vital role in supporting the smooth running of academic activities at XYZ University. However, many service issues still occur during operation. These include system delays, sudden class schedule changes, and suboptimal incident handling. The purpose of this study is to evaluate the capability level of XYZ University's Classroom Reservation system to manage service requests and incident handling, specifically the DSS02 (Manage Service Requests and Incidents) domain. The research method used is a case study with a quantitative approach through observation and the distribution of questionnaires based on the COBIT 5 Process Assessment Model (PAM). The results show that the DSS02 process capability level in its current condition is at Level 1 (Performed Process), while the expected condition is at Level 5 (Optimizing Process). Gap analysis shows a significant difference between the actual and expected conditions, especially in the aspects of process documentation, service performance measurement, and incident management. Therefore, to make the classroom reservation service support academic activities in a more efficient, effective, and reliable manner, planned and sustainable development efforts are needed.